Cardiorespiratory Fitness Is Associated With Better White Matter Integrity in Persons Living With HIV. (15th April 2022) - Kilgore, Collin B.; Strain, Jeremy F.; Nelson, Brittany; Cooley, Sarah A.; Rosenow, Alexander; Glans, Michelle; Cade, William Todd; Reeds, Dominic N.; Paul, Robert H.; Ances, Beau M.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Despite improved survival rates, neurocognitive impairment persists in persons living with HIV (PLWH). An active lifestyle is linked to improved cognition among PLWH, yet the neural substrates remain unclear. Diffusion tensor imaging and diffusion basis spectrum imaging measure HIV-related changes in brain white matter integrity. We used these measures of structural brain integrity to assess white matter changes, physical fitness, and cognition in a cross-sectional study of PLWH. Methods: Forty-four virologically well-controlled PLWH were recruited (average age of 56 years, a median recent CD4 + count of 682 cells/mm 3 ). Diffusion tensor imaging –derived fractional anisotropy (FA) and diffusion basis spectrum imaging–derived axonal density were calculated. Cardiorespiratory fitness [maximal volume of oxygen consumption (VO2 max)] was measured by performing indirect calorimetry during exercise to volitional exhaustion. Cardiovascular risk was assessed by the Framingham risk score. Neuropsychological performance (NP) testing evaluated learning, memory, psychomotor/processing speed, and executive function. Partial correlations assessed the relationships among cardiorespiratory fitness, neuroimaging, NP, and HIV clinical metrics (CD4 + count and time since diagnosis). Results: Higher VO2 max was associated with higher FA and higher axonal density in multiple white matter tracts, including the corticospinal tract and superior longitudinal fasciculus. Better NP in the motor/psychomotor domain was positively associated with FA and axonal density in diverse tracts including those associated with motor and visuospatial processing. However, higher VO2 max was not associated with NP or HIV clinical metrics. Conclusions: An active lifestyle promoting cardiorespiratory fitness may lead to better white matter integrity and decreased susceptibility to cognitive decline in virologically well-controlled PLWH.